2019
DOI: 10.4236/jss.2019.74002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Medical College Students’ Entrepreneurial Skills and Its Relationship with Social Intelligence

Abstract: Social intelligence and entrepreneurial skills are important factors influencing individual academic performance and career development. Studies have shown that people with high social intelligence have the ability to understand and manage others and have an advantage in innovation. The entrepreneurial personality trait is precisely the courage to innovate. Therefore, there is a close relationship between entrepreneurship and social intelligence. In this study, the author explores the relationship between stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The second hypothesis was confirmed: Greater entrepreneurial skills were associated with higher levels of all types of intelligence. This result is consistent with other studies, including the study by Wu and Wu (2019), who found a positive correlation between social intelligence and entrepreneurial skills in college students.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The second hypothesis was confirmed: Greater entrepreneurial skills were associated with higher levels of all types of intelligence. This result is consistent with other studies, including the study by Wu and Wu (2019), who found a positive correlation between social intelligence and entrepreneurial skills in college students.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies show that being proactive, taking risks, and innovativeness are key contributors to entrepreneurial success (Yasier et al, 2018). The literature also confirms the impact of entrepreneurial intentions on the behavior of business students (Yasir et al, 2018), on the success of their ventures (Duchek, 2018;Kim et al, 2018), and on their social intelligence (Wu & Wu, 2019).…”
Section: Related Literature and Scholarshipmentioning
confidence: 70%
See 1 more Smart Citation
“…In particular, in the knowledge economy era and industrial transformation, entrepreneurship can create more employment opportunities and promote socio-economic development. Meanwhile, with advancing Internet technology, Internet entrepreneurship has spread quickly with characteristics like low cost, low risk, and low threshold ( Wu and Wu, 2019 ). College Students are well aware that entrepreneurial activities are an important means of relieving employment pressure.…”
Section: Introductionmentioning
confidence: 99%
“…He defined social intelligence as the ability to understand and manage men, women, boys, and girls to act wisely in human relationships (Saffarinia Majid 2015). Wu, Wu (2019) consider social intelligence as the ability to establish interpersonal relationships (Saffarinia, Solgi. 2010).…”
Section: Introductionmentioning
confidence: 99%